Risk communication and social media during food safety crises: a study of stakeholders' opinions in Ireland. Issue 1 (2nd January 2016) - Regan, Áine; Raats, Monique; Shan, Liran Christine; Wall, Patrick G.; McConnon, Áine
Abstract : Social media is a particular communication platform which has witnessed an exponential growth in use and influence in recent years, democratising the communication process, and offering risk communicators a way of putting into practice those principles which are advocated to be at the core of risk management and communication. However, little is known about stakeholders' willingness to embrace this new form of communication in a food crisis. The current study presented an exploratory investigation of the opinions of Irish stakeholders on the position of risk communication in a crisis, with a particular focus on understanding what application social media may have. In-depth one-to-one interviews were carried out with key stakeholders holding frontline positions in managing and communicating about risk in the food sector in Ireland. The stakeholders identified risk communication as a central activity in a food safety crisis, driven by an obligation to protect both consumer health and the reputation of the Irish food sector. Stakeholders relied primarily on risk communication to disseminate information in a crisis so to educate and inform the public on a risk and to prevent confusion and alarmism; most did not explicitly value two-way risk communication in a crisis. The ability to effectively manage future crises may depend on stakeholders' willingness to adapt to the changing communication landscape, namely – their willingness to adopt social media and use it effectively. The findings indicate that the stakeholders interviewed are appreciative of the need to engage with social media in times of a food safety crisis. However, most valued social media as a one-way channel to help spread a message and there was little reference to the interactive nature of this medium. Implications for integrating social media into crisis risk communication strategies are discussed.